Management, risk factors and prognostic impact of checkpoint-inhibitor pneumonitis (CIP) in lung cancer – A multicenter observational analysis. (May 2023) - Frost, Nikolaj; Unger, Kristina; Blum, Torsten Gerriet; Misch, Daniel; Kurz, Sylke; Lüders, Heike; Olive, Elisabeth; Raspe, Matthias; Hilbrandt, Moritz; Koch, Myriam; Böhmer, Dirk; Senger, Carolin; et al.
Highlights: Incidence of checkpoint inhibitor pneumonitis (CIP) is highest in lung cancer. CIP mimics features from interstitial and infectious lung diseases. Incidence in 1.400 German lung cancer patients was 6.0% with 45% high-grade events. Thoracic radiotherapy directly targeting lung tissue is a key risk factor. Pretherapeutic diffusion capacity for carbon monoxide is an easy risk assessment. Abstract: Introduction: Checkpoint-inhibitor pneumonitis (CIP) represents a major immune-related adverse event (irAE) in patients with lung cancer. We aimed for the clinical characterization, diagnostics, risk factors, treatment and outcome in a large cohort of patients from everyday clinical practice. Patients and methods: For this retrospective analysis, 1, 376 patients having received checkpoint inhibitors (CPI) in any line of therapy from June 2015 until February 2020 from three large-volume lung cancer centers in Berlin, Germany were included and analyzed. Results: With a median follow-up of 35 months, all-grade, high-grade (CTCAE ≥ 3) and fatal CIP were observed in 83 (6.0%), 37 (2.7%) and 12 (0.9%) patients, respectively, with a median onset 4 months after initiation of CPI therapy. The most common radiologic patterns were organizing pneumonia (OP) and non-specific interstitial pneumonia (NSIP) (37% and 31%). All except 7 patients with G1-2 CIP interrupted treatment. Corticosteroids were administered to 74 patients with a median starting dose of 0.75 mg/kg. After complete restitution (n = 67), re-exposure to CPI (n = 14) led to additional irAE in 43% of the cases. Thoracic radiotherapy targeting the lung was the only independent risk factor for CIP (odds ratio 2.8, p < 0.001) and pretherapeutic diffusing capacity for carbon monoxide inversely correlated with CIP severity. Compared with patients without CIP and non-CIP irAE, CIP was associated with impaired overall survival (hazard ratios 1.23, p = 0.24 and 2.01, p = 0.005). Conclusions: High-grade CIP accounts for almost half of all CIP cases in an allcomer lung cancer population. A continuous vigilance, rapid diagnostics and adequate treatment are key to prevent disease progression associated with impaired survival.